STUDI KETINGGIAN KOLAM RETENSI SIMPANG POLDA PALEMBANG UNTUK LANGKAH PENENTUAN KEBIJAKAN - Sukemi -; Marlina Sylvia; samsuryadi samsuryadi; Hadipurnama Satria; Apriansyah Putra (Jurnal Informatika dan Rekayasa Elektronik, 2021)
Simpang Polda retention pond is an alternative flood control construction which is designed to temporarily hold exceeding water flow during rainfall in the vicinity of Simpang Polda, in order to avoid or reduce flood in the area. Retention ponds are prone to sedimentation due to garbage and other materials settling down in the bottom of the pond, which in turn causing reduction of total volume of water it can contain. To ensure that the pond has enough volume, depth measurements were done so that the pond can function as intended. Boat robots from previous research in 2019 and 2020 were utilized as the method to measure the depth of the retention pond. The boat robots mapped the depth of the whole pond area with the help of remote control and single beam sensor. Measurement result shows that the Simpang Polda retention pond has an average depth of 2.245 m. Based on this finding it is suggested that the local government water resource management agency (Dinas PUPR Dept. PSDA) to follow up with the appropriate sediment removal procedures to return the pond’s depth back to the original value when it was constructed